Emerging New‐Generation Detecting and Sensing of Metal Halide Perovskites. (6th February 2022) - Bu, Hui; He, Caili; Xu, Yanqing; Xing, Lu; Liu, Xiaomin; Ren, Shuxia; Yi, Shenghui; Chen, Liang; Wu, Hao; Zhang, Guanglei; Zhao, Jinjin; Shi, Jianlin
Abstract: The unique energy conversion characteristics of metal halide perovskite (MHP) materials, which can be hardly observed in conventional semiconductors and metal oxides, have boosted their promising application in detecting and sensing devices, in addition to their famous optoelectronic functions. Herein, the recent progresses of the state‐of‐the‐art applications of MHPs are focused on X‐ray diagnosis, cardiac detection, bionic retina, artificial synapse, cell imaging, and others. Owing to their emerging electrical properties with multifield coupled response effect, and photoelectric, electro‐optical, and all‐optical conversion functions, MHPs demonstrate promising prospects in the diagnosis and treatment of various diseases. As functional optoelectronic materials, MHPs provide a new platform for future biomedical devices. This review article is expected to present the current status on, and further promote the application of MHP materials in detecting and sensing devices. Abstract : Organometal halide perovskites present promising functions for detecting and sensing in biomedical applications due to their excellent energy conversion features. New‐generation detecting and sensing devices and materials are emerging with the fast development of metal halide perovskites, which demonstrate excellent functional features in X‐ray detection, medical sensing, bionic retina, artificial synapses, cell imaging, etc.